2012 9th IEEE Working Conference on Mining Software Repositories (MSR) 2012
DOI: 10.1109/msr.2012.6224284
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict types of code changes? An empirical analysis

Abstract: Abstract-There exist many approaches that help in pointing developers to the change-prone parts of a software system. Although beneficial, they mostly fall short in providing details of these changes. Fine-grained source code changes (SCC) capture such detailed code changes and their semantics on the statement level. These SCC can be condition changes, interface modifications, inserts or deletions of methods and attributes, or other kinds of statement changes. In this paper, we explore prediction models for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…We found a minor modification to value attribute (long integer allowed on value based features for instance). 13 We also found modifications to the allowed values on feature attribute "option" 14 as mentioned in Sect. 2, irrelevant in the context of this study.…”
Section: Threats To Validitymentioning
confidence: 91%
See 1 more Smart Citation
“…We found a minor modification to value attribute (long integer allowed on value based features for instance). 13 We also found modifications to the allowed values on feature attribute "option" 14 as mentioned in Sect. 2, irrelevant in the context of this study.…”
Section: Threats To Validitymentioning
confidence: 91%
“…We can find in the literature accounts of the issues arising during the evolution of such systems [1,19,42]. In a different domain, it has been shown that the analysis of fine-grained source code changes facilitates software maintenance [14]. Encouraged by such results, we propose to explore a similar idea in the context of highly variable software: observing the details of the fine-grained evolution of a feature model to derive information about the evolution of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Xiaoyan Zhu et al [22] have gathered a group of static metrics and modification data at class level from an open-source software product, Datacrow. Moreover, Emanuel Giger et al [24] have presented a paper for capturing the finegrained Source Code Changes (SCC) and their semantics and also Ali R. Sharafat and Ladan Tahvildari [25] have proposed a novel method for the prediction of changes in object oriented software system, in which the quality aspects were qualified by the probability of change in each class.…”
Section: Related Workmentioning
confidence: 99%
“…Sometimes, a full confusion matrix is more informative than reporting only the precision and recall [47]. Area under curve (AUC) is also a robust measure to assess and compare the performance of classifiers [26]. For example, using "accuracy" as a measure of prediction is problematic in heavily skewed distributions since it does not relate the prediction to the probability distribution of the classes, but AUC is insensitive to probability distributions [21].…”
Section: Comments From 5 Papers]mentioning
confidence: 99%